Judicial Activism in Regional Head Election Dispute: The Practice and Consistency of The Indonesian Constitutional Court - Amiruddin Amiruddin; Rizki Ramadani (Susbtantive Justice International Journal of Law, 2023)
The Constitutional Court's approach towards regional head election disputes is regarded as quite progressive and illustrates the growing trend of judicial activism. This article attempts to analyze the practice of activism by the Constitutional Court in the context of regional head election disputes and assess its consistency in simultaneous elections. This study uses a conceptual, statutory and case approach in analyzing several regional head election dispute decisions in 2020. The activism of the Constitutional Court in the context of regional head election disputes is at least practiced by judges through three things: first, the determination taken by the Constitutional Court to decide on re-voting and re-counting of votes; second, the willingness of the Court to consider election offenses that are structured, massive, and systematic; and third, the courage of judges to disqualify regional head candidates as well as determine the winner to provide legal certainty. This practice of activism is still being consistently pursued by judges in the 2020 simultaneous regional head elections. Even so, there is a tendency that structured, systematic and massive violations are not the main reason for terminating the election results, and even tend to be complicated by judges who demand more significant evidence. This condition will cause the burden of proving the structured, systematic and massive offenses to be much heavier in the future. This seems to be contradictory to previous decisions of the Constitutional Court which were known to prioritize substantive justice.